Structures, Biological Activities and Phylogenetic Relationships of Terpenoids from Marine Ciliates of the Genus Euplotes - Guella, Graziano (Molecular Diversity Preservation International, 2010)
In the last two decades, large scale axenic cell cultures of the marine species comprising the family Euplotidae have resulted in the isolation of several new classes of terpenoids with unprecedented carbon skeletons including the (i) euplotins, highly strained acetylated sesquiterpene hemiacetals; (ii) raikovenals, built on the bicyclo[3.2.0]heptane ring system; (iii) rarisetenolides and focardins containing an octahydroazulene moiety; and (iv) vannusals, with a unique C(30) backbone. Their complex structures have been elucidated through a combination of nuclear magnetic resonance spectroscopy, mass spectrometry, molecular mechanics and quantum chemical calculations. Despite the limited number of biosynthetic experiments having been performed, the large diversity of ciliate terpenoids has facilitated the proposal of biosynthetic pathways whereby they are produced from classical linear precursors. Herein, the similarities and differences emerging from the comparison of the classical chemotaxonomy approach based on secondary metabolites, with species phylogenesis based on genetic descriptors (SSU-rDNA), will be discussed. Results on the interesting ecological and biological properties of ciliate terpenoids are also reported.